AUTHENTIC LEADERSHIP: SCIENTIFIC PRODUCTION ANALYSIS AND MEASUREMENT SCALES - PIOLI,BARLA L. T. (2020)
ABSTRACT Purpose: This paper analyzes the publications on the “authentic leadership” construct, based on systematic literature review and bibliometric analysis techniques, and aims to identify and analyze data regarding the chronology of publications, the identification of the most prolific journals and authors, research approaches, and the existence of authentic leadership measurement/assessment tools and its applications, besides analyzing the construction of these tools. Originality/value: Of the 431 articles analyzed, those dealing with reviews of literature do not present bibliometric data associated with the analysis of the construct measurement instruments. Design/methodology/approach: A literature review was performed systematically, using the query “authentic leadership” on the Academic Search Premier (Ebsco), Scopus, and Web of Science databases, with no starting date delimitation, with the deadline of December 2018, which resulted in the identification of 1390 articles. After eliminating duplicates and three filters, 431 documents remained for analysis. Findings: Three specific construct measurement/assessment tools were identified: the Authentic Leadership Questionnaire (ALQ), the Authentic Leadership Inventory (ALI), and the Authentic Leadership Integrated Questionnaire (AL-IQ). There is a predominance of quantitative studies from 2008, with a wide application of ALQ. Instruments of quantitative measurement of authentic leadership did not emerge, only tools that evidence the presence of authenticity of leaders.